Declining childhood and adolescent cancer mortality. Issue 16 (22nd May 2014) - Smith, Malcolm A.; Altekruse, Sean F.; Adamson, Peter C.; Reaman, Gregory H.; Seibel, Nita L.
<x xml:space="preserve">Abstract</x> BACKGROUND To evaluate whether progress continues in identifying more effective treatments for children and adolescents with cancer, the authors examined both overall and disease‐specific childhood cancer mortality rates for the United States, focusing on data from 2000 to 2010. METHODS Age‐adjusted US mortality trends from 1975 to 2010 were estimated using joinpoint regression analysis. Analyses of annual percentage change (APC) were performed on the same diagnostic groupings for the period restricted to 2000 through 2010 for groupings ages <20 years, <15 years, and 15 to 19 years. RESULTS After a plateau in mortality rates during 1998 to 2002 (APC, 0.3%), the annual decline in childhood cancer mortality from 2002 to 2010 (APC, −2.4%) was similar to that observed from 1975 to 1998 (APC, −2.7%). Statistically significant declines in mortality rates from 2000 to 2010 were noted for acute lymphoblastic leukemia, acute myeloid leukemia, non‐Hodgkin lymphoma, Hodgkin lymphoma, neuroblastoma, central nervous system cancers, and gonadal cancers. From 2000 to 2010, the rates of decline in mortality for the group ages 15 to 19 years generally were equal to or greater than the rates of decline for the group ages birth to 14 years. Improvements in treatment since 1975 resulted >45, 000 cancer deaths averted through 2010. CONCLUSIONS Cancer mortality for both children and adolescents declined from 2000 to 2010, with significant declines observed for multiple cancer types. However, greater than 1900 cancer deaths still occur each year among children and adolescents in the United States, and many survivors experience long‐term effects that limit their quality of life. Continued research directed toward identifying more effective treatments that produce fewer long‐term sequelae is critical to address these remaining challenges. Cancer 2014;120:2497–2506. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.